[Rezension von: Barrett, Ron, Aghor medicine] - Sax, William Sturman (The journal of Asian studies, 2011)
Aghor Medicine: Pollution, Death, and Healing in Northern India. By Barrett Ron. Berkeley and Los Angeles: University of California Press, 2008. xxii, 216 pp. $39.99 (cloth); $24.95 (paper). - Volume 70 Issue 3 - William S. Sax
Gesehen am 22.03.2018
Keywords: Rezension